Meaning of Happiness in Children: an Exploratory Study - Rahmatika Kurnia Romadhani (Psychological Research and Intervention, 2020)
The aim of this research was to explore what makes children happy. The study was a survey on the number of 64 elementary students. An open-ended questionnaire was used to learn what makes children happy. The data was analyzed using preliminary coding, categorization, axial coding, and selective coding. The respondents’ answers were analyzed using descriptive analysis. Result showed that there were two elements of the source of children happiness, those are (1) Self-fulfillment (95.54%) consisting of doing activity, doing hobby, leisure time, achievement, gift; (2) Relations with others (4.46%) consist of relations with family and friends. This study gave insight that self-fulfillment is an important source of happiness in children. This study shows that all are nothing but social engagement.